The Effect of Debt to Equity Ratio on Total Assets at PT Bank SUMUT Center Medan City Period 2020 to 2022 - Setia Budi Putra Lase; Hendry (PT FORMOSA CENDEKIA GLOBAL, 2024)
In analyzing the financial condition of a company, it is very important to analyze financial ratios. Where financial ratios have an important role in knowing how much influence financial conditions have on the company's better future. This study was conducted to obtain empirical evidence regarding the effect of Debt To Equity Ratio on Total Assets at PT Bank Sumut Pusat Medan City. Data acquisition is generated from secondary data calculated in each month on the financial statements studied at PT Bank Sumut Pusat Kota Medan. Data collected by interview and data management and analyzed by multiple linear regression analysis, in this study the data was processed using SPSS. The sample used in this study was 36 monthly reports for three years, namely the period 2020 to 2022. The results of this study indicate that partially Debt to Equity Ratio (DER) has a significant effect on Total Assets at PT Bank Sumut Medan City Center for the period 2020 to 2022